Determinants of crop diversification among smallholder farmers within marshes around Bukavu, Eastern DR Congo - Arsene, Mushagalusa Balasha; Rodrigue, Adrien Lugendo; Bitagirwa, Aloise; Kulumbu, John Tshomba; Fyama, Jules Nkulu Mwine (Publisher of Widyagama University of Malang (UWG Press), 2023)
In the South Kivu province of the democratic republic of Congo, smallholder farmers have been draining marshlands for years to grow a variety of crops into a mixed cropping system. This study based on interviews with smallholder farmers examines the drivers of crop diversification and the challenges these farmers face in marshes where various crops are grown for food and income security. Results showed that in these marshy landscapes, crop diversification system is traditionally rooted in local farming practices (84%), and this is designed to meet farmers’ self-consumption and market objectives (72%), and also withstand risks associated with the changing climate and pest outbreaks (91%). Further, results from the logistic regression showed that farming experience, farm size, and livestock ownership influence significantly farmers ‘decisions to diversify crops. However, farmers claimed to face increasing prices of agricultural inputs (73%) and unusual crop theft (32%) during this ongoing COVID-19 pandemic whereas floods and pest attack as well as plant diseases are raising more concerns among farmers. Although farmers acknowledged the significant roles of livestock in easily acquiring manure and mulch to improve croplands, they still requested specific interventions in terms of priorities (e.g drainage equipment, pest management information) to strengthen the resilience and sustainability of agriculture within marshes.JEL Classification Q01; Q10; R14